Improving Students' Learning Achievement Through Cooperative Learning and Padlet Application in Class XI MIPA 3 - Rulianah, Nita; Prabowo, Agung; Sukono, Sukono (International Journal of Ethno-Sciences and Education Research, 2022)
Chemistry learning is still less active which can be seen t students tend to be passive and less enthusiastic in learning. Students participate in learning activities with less enthusiasm and tend to wait for explanations from the teacher. One of the solutions used to overcome this is the cooperative learning model and the use of padlet application media. The purpose of this study was to find out the application of cooperative learning and padlet application media in class XI MIPA 3. The research sample was students in class XI MIPA 3 SMA N 1 Mirit, Kebumen consisting of 36 students. The research was conducted in 3 meetings. This type of research is quantitative research using descriptive analysis. Screening data through pretest and posttest value data. The results showed that learning using cooperative learning and padlet applications increased 30.94% of student achievement in class XI MIPA 3 SMA N 1 Mirit.